The association between medication adherence and blood pressure control among hypertensive patients attending a tertiary hospital in south-south Nigeria - Ozumba, Lillian N.; Ndukwu, Geraldine U. (International Journal of Research in Medical Sciences, 2021)
Background: Hypertension is a common disease among adults. It is a global health condition that requires drugs and lifestyle changes for its management and control. Despite this, the rate of hypertension related deaths has been increasing in prevalence across the world. The purpose of this paper is to determine the association between medication adherence and blood pressure control among hypertensive patients in Family Medicine Clinic, University of Port Harcourt Teaching Hospital, Rivers State, Nigeria. Methods: A hospital based cross-sectional study was conducted in Family Medicine Clinic, University of Port Harcourt Teaching Hospital. Systematic sampling method was used to select 400 participants. A structured questionnaire namely Morisky Medication Adherence Scale-4 was adapted and used for data collection in this study. Bivariate analysis was done using Chi square test and odd ratio. Results: A total of 400 (118 males and 282 females) adult hypertensive patients participated in this study. Majority of the participants had poor adherence to medication treatment 71.2% (n=285), whereas the remaining ones 28.8% (n=115) had good adherence. Similarly, most of the participants, 77.2% (n=309) had poor blood pressure control while the remainder 22.8% (n=91) experienced the opposite. The bivariate analysis showed that good medication adherence was significantly associated with good blood pressure control. Conclusions: Medication adherence was low especially among those with poor blood pressure control. This link was statistically significant therefore doctor-patient interaction with emphasis on medication adherence is advocated.